2014
DOI: 10.1371/journal.ppat.1004018
|View full text |Cite
|
Sign up to set email alerts
|

Role of Calmodulin-Calmodulin Kinase II, cAMP/Protein Kinase A and ERK 1/2 on Aeromonas hydrophila-Induced Apoptosis of Head Kidney Macrophages

Abstract: The role of calcium (Ca2+) and its dependent protease calpain in Aeromonas hydrophila-induced head kidney macrophage (HKM) apoptosis has been reported. Here, we report the pro-apoptotic involvement of calmodulin (CaM) and calmodulin kinase II gamma (CaMKIIg) in the process. We observed significant increase in CaM levels in A. hydrophila-infected HKM and the inhibitory role of BAPTA/AM, EGTA, nifedipine and verapamil suggested CaM elevation to be Ca2+-dependent. Our studies with CaM-specific siRNA and the CaM i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 52 publications
2
36
0
Order By: Relevance
“…Besides, intracellular Ca 2+ overload could upregulate the expression of several down-stream proteins. In the situation of ischemic myocardial stress response, CAMKIIα could activate ERK and NF-κB, thus regulating inflammation and injury[12]. In our study, as shown in Fig 3, CoCl 2 treatment disrupted the intracellular Ca 2+ hemostasis and inducing the phosphorylation of CAMKIIα, ERK and NF-κB.…”
Section: Discussionsupporting
confidence: 53%
“…Besides, intracellular Ca 2+ overload could upregulate the expression of several down-stream proteins. In the situation of ischemic myocardial stress response, CAMKIIα could activate ERK and NF-κB, thus regulating inflammation and injury[12]. In our study, as shown in Fig 3, CoCl 2 treatment disrupted the intracellular Ca 2+ hemostasis and inducing the phosphorylation of CAMKIIα, ERK and NF-κB.…”
Section: Discussionsupporting
confidence: 53%
“…Therefore, to examine whether increased ROS and RNS generation observed earlier is a prerequisite to apoptosis production in CTM cells, the apoptotic population by flow cytometry using Annexin-V/PI assay was ascertained. A. hydrophila mediated apoptosis has been earlier reported in murine macrophages and head kidney macrophages of fish (Mazumdar et al, 2004;Banerjee et al, 2012;Banerjee et al, 2014a). However, there are no existing reports of the apoptosis induction in the thymic macrophages in response to A. hydrophila challenge.…”
Section: Discussionmentioning
confidence: 97%
“…Besides, it has been fairly well reported that the ROS accumulation plays a crucial role in A. hydrophila induced macrophage apoptosis (Fierro-Castro et al, 2012;Chakrabarti et al, 2014). ROS generation in macrophages initiates a series of reactions including iNOS mediated NO production leading to biomolecular damage, apoptosis and release of cytokine cascade (Banerjee et al, 2014a). In-vitro piscine macrophage models can thus serve as an excellent platform for exploring several distinct mechanisms of disease progression (Hightower and Renfro, 1988;Fierro-Castro et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Altered Ca 2+ -homeostasis is primal to ER-stress. After observing Ca 2+ and its dependent molecules critical for A. hydrophila -induced HKM apoptosis46 we questioned the involvement of ER-stress in terms of CHOP-BiP-eIF2α-spree and caspase-12 activation.…”
Section: Discussionmentioning
confidence: 99%
“…A. hydrophila -induced macrophage apoptosis is executed by an intracellular proteolytic cascade of caspases, where initiator caspases are triggered by a range of intracellular signalling molecules to accomplish programmed demolition of cell through caspase-3 activation346. As an early initiator of the process, the role of calcium (Ca 2+ ) is foremost7.…”
mentioning
confidence: 99%